Radical news? Immigrants' television use, acculturation challenges, and support for terrorism. (2nd October 2021) - Schumann, Sandy; Osborne, Danny; Gill, Paul; Fell, Benjamin F.; Hewstone, Miles
ABSTRACT: Previous research shows that acculturation challenges predict immigrants' support for terrorism. Here, we acknowledge the central role of mass media use in the acculturation process. We investigate whether immigrants who infrequently use ethnic and host country media, a possible indicator or driver of marginalisation, report higher sympathy with terrorism than frequent media users. We further examine if those who prefer ethnic over host country media, which might reflect or facilitate disengagement from the host society, support terrorism more strongly. To address these research questions, we conducted secondary analyses of a public opinion poll of Muslim immigrants resident in the United Kingdom ( N  = 880). Focusing on immigrants' use of ethnic and host country television channels, latent class analysis identified four groups: Frequent and Infrequent Media Users as well as Ethnic and Host Country Media Users. Overall sympathy with terrorism was low. Contesting our hypothesis, Frequent Media Users supported terrorist action more than Infrequent Media Users. Ethnic Media Users also expressed higher sympathy with terrorism than Host Country Media Users. Findings emphasise the dynamic interplay between media use and acculturation challenges; they further suggest strategies to reduce immigrants' support for terrorism.